Pragmatic Realism, Religious Truth, and Antitheodicy On Viewing the World by Acknowledging the Other - Pihlström, Sami (Helsinki University Press, 2020)
Both as a traditional theological issue and in its broader secular varieties, theodicy remains a problem in the philosophy of religion. In this book, Professor Sami Pihlström provides a novel critical reassessment of the theodicy discourse addressing the problem of evil and suffering. He develops an antitheodicist view, arguing that theodicies seeking to render apparently meaningless suffering meaningful or justified from a "God's-Eye-View" ultimately rely on metaphysical realism failing to recognize the individual perspective of the sufferer. Pihlström thus shows that a pragmatist approach to the realism issue in the philosophy of religion is a vital starting point for a re-evaluation of the problem of theodicy.